PENDAMPINGAN PEMBUATAN HAND SANITIZER ALAMI SEBAGAI SALAH SATU UPAYA PENCEGAHAN TBC PADA MASYARAKAT PAYAMAN GIRIMULYO IMOGIRI BANTUL YOGYAKARTA - Rahmawati, Ullya; Rahayu, Muji; Windarso, Sardjito Eko; Widyantoro, Wahyu; Nuryati, Anik; Nuryani, Siti; Pudyastuti, Rita Rena (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
TBC cases in Indonesia continue to increase. One way to prevent transmission of TBC is to wash your hands with soap or hand sanitizer. Hand sanitizers on the market contain many antiseptics in the form of synthetic chemicals which can cause skin health problems, besides being relatively expensive. For this reason, it is necessary to develop hand sanitizers made from natural ingredients that are safe, cheap and easy to make with simple equipment and have economic value. Some natural ingredients that can be used in making natural hand sanitizers include betel leaf, lime, orange peel, aloe vera and several studies have also mentioned natural ingredients such as basil leaves, kecombrang flowers, banana fronds, aloes. These natural ingredients contain several active ingredients such as saponins, tannins, flavonoids, citric acid, polyphenols, alkaloids which function as an antiseptic capable of killing pathogenic organisms. The aim of the activity is to provide knowledge to the public about hand sanitizers and how to make hand sanitizers with natural ingredients. as well as the application of making natural hand sanitizers independently. The method used is counseling/ lectures/ material explanations accompanied by discussions and demonstrations of making hand sanitizers. The result of this community service is an increase in the participants' knowledge from 80-90% correct answers to 100% and 100% of the participants practice making natural hand sanitizers, the participants are also committed to implement and apply the manufacture of natural hand sanitizers in their respective homes using various materials from plants that are easy to get around the neighborhood such as betel, aloe vera and lime.